Pengembangan eco enzyme berbasis limbah organik melalui penerapan eco community (Development of eco enzyme based on organic waste through application of eco community) - Hanum, Zuraida; Yurliasni, Yurliasni; Wajizah, Sitti; Aini, Zahratul; Delima, Mira (Universitas Syiah Kuala, 2022)
Application of the 3Rs in the form of reuse, reduce, and recycle organic waste is the best program in environmental conservation, because it prioritizes the treatment of organic waste from its source. One form of recycling market organic waste by its utilization in the form of Eco Enzyme (EE). The treatment of market organic waste had been carried out by Dayah Baitul Qur'an to gain self-supporting funds for Dayah's operational necessity by producing and marketing EE products. The training covered several activities, mainly increasing knowledge (cognitive aspect) and changing habits (affective aspect) and practices (psychomotor aspect). The degree of understanding measurement was carried out by pre-test and post-test using the Likert scale. Based on pre-test results, the lowest score of 4 and the highest 9, with the modus value of 6 (31.25%) and the average value was 59.38%, classified as a moderate degree of understanding on the Likert scale. The post-test resulted in the lowest score of 7 and the highest 10, with the modus value of 10 (62.50%) and the average value was 93.33%, classified as an excellent degree of understanding on the Likert scale. Based on the activity results, it can be concluded that the Eco Enzyme Service based on organic waste increases public understanding of waste management and the economic benefits of organic waste treatment.